Integrasi Chatbot Berbasis GPT Terhadap Website E-Commerce (Studi Kasus Toko JSA) - Teguh Pramana, Made Putra; Rahayuda, I Gede Surya (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023, 2023)
A website is a series of sites with related hyperlinks that individuals, organizations, companies, or government made. E-commerce websites are websites that have features for transaction through online services. Toko Jsa Emas Perak is one of the companies that want to develop its company's presence on the internet using e-commerce websites. Uniqueness is important to have an edge between online competition. By implementing a chatbot system in the e-commerce website, it can increase the effect on each user in interaction. the propose of this research is to implement a chatbot service in the toko jsa website.